Tuberculosis of the genitourinary tract: Imaging features with pathological correlation - Malai Muttarak (2018)
The prevalence of pulmonary and extrapulmonary tuberculosis (TB) has been increasing over the past decade, due to the rising number of people with acquired immunodeficiency syndrome and the development of drug-resistant strains of Mycobacterium tuberculosis. The genitourinary tract is the most common site of extrapulmonary TB. Diagnosis is often difficult because TB has a variety of clinical and radiological findings. It can mimic numerous other disease entities. A high level of clinical suspicion and familiarity with various radiological manifestations of TB allow early diagnosis and timely initiation of proper management. This pictorial essay illustrates the spectrum of imaging features of TB affecting the kidney, ureter, bladder, and the female and male genital tracts.